Comparison between Static Stretching Exercises and Eccentric Muscle Energy Techniques in Upper Cross Syndrome: Randomized control trial: Static Stretching Exercises and Eccentric Muscle Energy - Irshad , Asima; Fahad Khan , Muhammad; Khan, Mehwish; Rabia, Kaniz; Aslam, Javeria; Zafar, Ibraheem; Masood, Ramsha; Naz , Iqra; Aslam, Maimoona; Nazir, Ammanullah (Pakistan BioMedical Journal, 2022)
Neck pain is the most common complaint and Cervical pain is more common in middle-aged women than in males. The most prevalent reason for patients to seek medical attention is neck pain. Objective: To identify the effectiveness of stretching and muscle energy techniques along with mobilization of cervical segment in the management of upper cross syndrome.Methods: The randomized controlled experiment took place from August 2018 to January 2019 at Benazir Bhutto Orthopedic and Rehabilitation Centre in Pakistan (Rawalpindi) and included patients with upper cross syndrome that were randomly consigned to two equal groups using a lottery system. The Group-A patients management is eccentric muscular energy therapy with cervical segmental mobilization, although Group-B patients treatment protocol is static stretching exercises accompanied by segmental mobilization of cervical spine . Each patient received two sessions each week for three weeks, during which their visual analogue scale, and neck disability index were measured. An inclinometer was used to measure the cervical passive range of motion. Data was collected at the commencement of the study and again after three weeks of treatment. SPSS 21 was used to analyze the data. Results: Twenty (20%) of the 40 individuals were in each of the two groups. The average age in Group-A was 42.7511.13 years. It remained 40.509.14 years in Group-B. On all metrics, the eccentric muscular energy technique and static stretching approach equally demonstrated substantial results that is P Value is less than 0.05.Conclusion: Both approaches were shown to be equally successful in lowering neck impairment, enhancing cervical range of motion, and decreasing pain